The effect of concussion on batting performance of major league baseball players - Chow, B. H.; Stevenson, A. M.; Burke, J. F.; Adelman, E. E. (Open Access Journal of Sports Medicine, 2019)
Purpose: Previous investigations into concussions` effects on Major League Baseball (MLB) players suggested that concussion negatively impacts traditional measures of batting performance. This study examined whether post-concussion batting performance, as measured by traditional, plate discipline, and batted ball statistics, in MLB players was worse than other post-injury performance. Subjects and methods: MLB players with concussion from 2008 to 2014 were identified. Concussion was defined by placement on the disabled list or missing games due to concussion, post-concussive syndrome, or head trauma. Injuries causing players to be put on the disabled list were matched by age, position, and injury duration to serve as controls. Mixed effects models were used to estimate concussion`s influence after adjusting for potential confounders. The primary study outcome measurements were: traditional (eg, average), plate discipline (eg, swing-at-strike rate), and batted ball (eg, ground ball percentage) statistics. Results: There were 85 concussed players and 212 controls included in the analyses. There was no significant difference in performance between concussed players and controls. However, concussed players started at a lower level of performance pre-event than the controls, striking out a 9.2% rate vs 8.2% (P=0.042) with an isolated power of 0.075 vs 0.082 (P=0.035). For concussed players, traditional batting statistics decreased before plate discipline metrics. Conclusion: MLB players` performance was lower after return from concussion, but no more than after return from other injuries. The decreased performance prior to concussion suggests that concussion-related performance declines may not be due exclusively to concussion and perhaps point to risk factors predisposing to concussion.